Euro area: Single currency - national money creation - Stefan Kooths; Björn van Roye (Kiel Institute for the World Economy (IfW), 2012)
The Eurosystem has been pursuing a crisis management policy for more than four years now. This policy aims primarily at maintaining financial stability in the euro area by providing vast liquidity support to commercial banks that are operating in nationally segmented banking systems. As a side effect, the national central banks substitute money market operations for cross-border capital flows. The national central banks are thus increasingly engaging in substantial balance-of-payments financing, and financial risks are being shifted from investors to European taxpayers via the Eurosystem. Symptomatically, this shows up in exploding TARGET2 positions in the national central banks' balance sheets. The longer this process continues, the stronger the centrifugal forces become that ultimately might break up the single currency. Instead of a fiscal union, a euro-area-wide regulatory approach is required. In addition to establishing a uniform scheme for banking regulation, supervision and resolution, we recommend that contingent convertible bonds (CoCos) be introduced to provide a major source of refinancing for the banking industry. Since CoCos cannot be introduced overnight, national and European banking resolution funds would be needed in the short run. These funds would not rescue banks but they would kick in as soon as a bank's equity is depleted in order to wind up failing banks in a systemically prudent way.
Keywords: E42; E51; E58; F32; F34; 330; Balance-of-payments financing; Target2; Eurosystem; Monetary policy; Financial crisis; Euro area; Financing mechanisms; Europäische Wirtschafts- und Währungsunion; Verrechnungsverkehr; Internationaler Zahlungsverkehr; Zahlungsbilanzungleichgewicht; Geldpolitik; Geldschöpfung; Ordnungspolitik; Bankenpolitik; Eurozone